1998
DOI: 10.1074/jbc.273.42.27587
|View full text |Cite
|
Sign up to set email alerts
|

The Bloom's Syndrome Helicase Unwinds G4 DNA

Abstract: BLM, the gene that is defective in Bloom's syndrome, encodes a protein homologous to RecQ subfamily helicases that functions as a 3-5 DNA helicase in vitro. We now report that the BLM helicase can unwind G4 DNA. The BLM G4 DNA unwinding activity is ATP-dependent and requires a short 3 region of single-stranded DNA. Strikingly, G4 DNA is a preferred substrate of the BLM helicase, as measured both by efficiency of unwinding and by competition. These results suggest that G4 DNA may be a natural substrate of BLM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
428
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(447 citation statements)
references
References 34 publications
16
428
2
1
Order By: Relevance
“…DNA crosslinking within GC-rich region in mammalian chromosomes can create quadriradials (Matsumoto et al, 1999). Previous work has shown that BLM is a general helicase with preference for G4 DNA formed in a single stranded G-rich region exposed by recombination (Sun et al, 1998). As shown in Table 1, UVC irradiation in G 1 to early S phase caused chromosomal aberrations and a defect in BLM resulted in a remarkable enhancement of quadriradial formation in DT40 cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…DNA crosslinking within GC-rich region in mammalian chromosomes can create quadriradials (Matsumoto et al, 1999). Previous work has shown that BLM is a general helicase with preference for G4 DNA formed in a single stranded G-rich region exposed by recombination (Sun et al, 1998). As shown in Table 1, UVC irradiation in G 1 to early S phase caused chromosomal aberrations and a defect in BLM resulted in a remarkable enhancement of quadriradial formation in DT40 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Because BLM 7/7 cells showed hypersensitivity to bleomycin but not to X-ray irradiation, the defect in BLM may induce hypersensitivity to mutated adducts of DNA without increasing the sensitivity to DNA strand breaks. Previous work has shown that Gquadruplex DNA (G4 DNA) junctions are a preferred substrate of BLM, as measured by the e ciency of unwinding (Sun et al, 1998). G4 DNA is assumed to be formed in a single stranded G-rich region exposed by recombination or replication.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate here that the helicase activity of BLM regulates CDA promoter function either directly or indirectly. The preferred substrates for the recombinant BLM protein are G-quadruplex structures 18,19 . However, we identified no potential intramolecular G-quadruplex-forming sequences or particular sequences likely to form secondary structures in the CDA promoter (using Quad Parser, website http://www.quadruplex.com), suggesting that CDA expression is not repressed by secondary structures formed in the absence of BLM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PML, these ALT-associated PML nuclear bodies (APBs) contain many other proteins that form ring-like structures around the telomeric DNA that may negatively influence DNA folding or affect BRACO-19 binding. Furthermore, some of these proteins present at telomeres of ALT ϩ cells include the BLM and WRN RecQ helicases that bind telomeric DNA (60-62) and can unwind G-quadruplex structures (63)(64)(65), thereby limiting the potential number of G-quadruplex structures. Considering that ligands that stabilize G-structures are also reported to inhibit the processivity of these enzymes (66), the net in vivo impact of G-quadruplex unfolding by helicases and stabilization by BRACO-19 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%